Potential Toxicity Evaluation of Protopine in Macleaya cordata (Willd.) R. Br.—A Bioactivity Guided Approach - Hu, Wanjun; Yang, Fan; Liu, Weixue; Guo, Liyang; Ai, Liwen; Zhang, Xiaomeng; Sheng, Zunlai; Gao, Chunbo (Frontiers in Veterinary Science, 2021)
Macleaya cordata (Willd.) R. Br. (M. cordata) is a perennial herb known for its chemotherapeutic properties, strong feeding additive, and potential antidiarrheal drug. Despite its therapeutic potentials, its clinical applications are hindered by an apparent lack of toxicity data. In this study, the toxic ingredients of this plant were investigated using a bioactivity-guided approach. Two compounds, protopine and allocryptopine, were purified and elucidated by LC-MS, 1H-NMR, and 13C-NMR. Protopine, a primary component in M. cordata, had an LD50 of 313.10 mg/kg i.g., which was considered toxic. An autopsy was performed on protopine-administered mice, and the histopathology of the kidney, liver, brain, heart, lung, and spleen was determined. Autopsy findings included hemorrhage in the respiratory system, lung congestion, and hemorrhage and edema in the parenchymatous organs (heart, liver, kidney, and brain). Histopathology confirmed the pathological changes in the brain, liver, and kidney. Protopine is one of the principal bioactive constituents of many phytopreparations used in veterinary and human medicine, such as Sangrovit and Iberogast. Our findings indicated that phytopreparations containing protopine might pose a serious health threat to humans and animals.